2013
DOI: 10.1007/s00404-013-2953-2
|View full text |Cite
|
Sign up to set email alerts
|

Elevated diastolic blood pressure in insulin-resistant polycystic ovarian syndrome patients

Abstract: We hypothesize that hyperlipidemia and IR may be involved in the pathophysiologic features of the elevated diastolic blood pressure in PCOS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
1
0
0
1
Order By: Relevance
“…A cross-sectional study of 84 patients with PCOS reported higher levels of arterial stiffness, thickness of the carotid intima-media due to hyperlipidaemia and insulin resistance, thereby increasing diastolic function 25 and elevated diastolic blood pressure 26 . Similarly, we noted a highly significant (p < 0.001) increase in the diastolic and mean blood pressures of PCOS patients.…”
Section: Discussionsupporting
confidence: 72%
“…A cross-sectional study of 84 patients with PCOS reported higher levels of arterial stiffness, thickness of the carotid intima-media due to hyperlipidaemia and insulin resistance, thereby increasing diastolic function 25 and elevated diastolic blood pressure 26 . Similarly, we noted a highly significant (p < 0.001) increase in the diastolic and mean blood pressures of PCOS patients.…”
Section: Discussionsupporting
confidence: 72%
“…11 Wartość ciśnienia rozkurczowego krwi jest niższa w grupie kobiet zmagających się z PCOS bez towarzyszącej insulinooporności w porównaniu z kobietami, u których rozpoznano zarówno to schorzenie, jak i stwierdzono insulinooporność. 31 Dodatkowo hiperinsulinemia jest odpowiedzialna za wzrost resorpcji sodu i zaburzenie natriurezy poprzez aktywację układu renina -angiotensyna -aldosteron. 11,32 Stężenie całkowitego i wolnego testosteronu, który w zespole PCOS jest nadmiernie wydzielany, koreluje z wartościami skurczowego i rozkurczowego ciśnienia tętniczego krwi, niezależnie od wieku, insulinooporości, otyłości i dyslipidemii.…”
Section: Ryzyko Kardiometaboliczne W Pcosunclassified